2021
DOI: 10.1007/s00445-021-01497-6
|View full text |Cite
|
Sign up to set email alerts
|

Sink or float: microtextural controls on the fate of pumice deposition during the 2012 submarine Havre eruption

Abstract: Silicic submarine volcanic eruptions can produce large volumes of pumices that may rise buoyantly to the ocean surface and/or sink to the seafloor. For eruptions that release significant volumes of pumice into rafts, the proximal to medial submarine geologic record is thus depleted in large volumes of pumice that would have sedimented closer to source in any subaerial eruption. The 2012 eruption of Havre volcano, a submarine volcano in the Kermadec Arc, presents a unique opportunity to study the partitioning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…However, the common occurrence of the black pumice coexisting with the gray type with clear boundary strongly indicates that the black pumice played certain roles in the explosive eruption of FOB in 2021. Mitchell et al (2021) suggested that the pumice clasts form a floating raft and those that suddenly sink to the seafloor have distinct micro‐textures (i.e., the floating pumice has a higher vesicle number density and lower pore space connectivity). This could bias the pumice clasts that were sampled.…”
Section: Discussionmentioning
confidence: 99%
“…However, the common occurrence of the black pumice coexisting with the gray type with clear boundary strongly indicates that the black pumice played certain roles in the explosive eruption of FOB in 2021. Mitchell et al (2021) suggested that the pumice clasts form a floating raft and those that suddenly sink to the seafloor have distinct micro‐textures (i.e., the floating pumice has a higher vesicle number density and lower pore space connectivity). This could bias the pumice clasts that were sampled.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). Pumice has a large surface area with many vesicles 40 42 . When pumice stones are impacted onto solid surfaces such as by wave action, they may break apart, thus enlarging the surface area and leading to a dramatic increase in available bacterial habitat; pumice may continue to serve as an ecosystem mediator for a long period of time.…”
Section: Resultsmentioning
confidence: 99%
“…Embedded rock fragments are virtually unique to the raft banded pumice (see also Mitchell et al, 2021). Readily observable angular rock fragments are lapilli-sized (4-10 mm), but some are <2 mm in size (Figure 2).…”
Section: Embedded Rock Fragmentsmentioning
confidence: 96%
“…An effusive exit velocity of approximately 14 ms −1 was estimated to produce the pumice raft based on magma ascent models inputting seafloor pumice properties (Manga et al, 2018). However, more recent work has shown that when only utilizing seafloor pumice properties, eruption rates of the associated pumice rafts could be considerably underestimated (Knafelc et al, 2020;Mitchell et al, 2021;Knafelc et al, 2022). Most recently, the Havre 2012 eruption model has been expanded to include a shortlived, violent explosive eruption, capable of ejecting hot pyroclasts through the 900 m water column into the atmosphere, which then air-cooled to be deposited at the ocean surface, producing the pumice raft (Knafelc et al, 2022).…”
Section: The Havre 2012 Eruptionmentioning
confidence: 99%
See 1 more Smart Citation